Dynamic Performance Analysis of Adaptability of Gauge Changeable High-speed EMUs - Guodong LI; Jing ZENG; Xiaofeng LI; Yi LYU (机车电传动)
Gauge changeable high-speed EMUs need to adapt to gauge changes, rail profile and gradient changes, to meet the high-speed operation stability and other dynamic performance requirements. Due to additions of gauge-changing mechanism and increasing the unsprung weight, the adaptability of the gauge changeable EMUs to these changes was calculated and analyzed. The calculation results showed that the gauge changeable EMUs have good adaptability to gauge, rail profile, rail bottom slope and unsprung weight, which met the design requirement.